Improved delivery of natural alkaloids into lung cancer through woody oil-based emulsive nanosystems - Jing Zhao; Shan Liu; Xueyuan Hu; Yunmei Zhang; Shenglei Yan; Hua Zhao; Mei Zeng; Yao Li; Lan Yang; Jingqing Zhang (Taylor & Francis Group, 2018)
Most antitumor ingredients found in nature have poor solubility. These ingredients are expected to have much better absorption and higher bioavailability than synthetic antitumor agents. Woody oil emulsive nanosystems carrying poorly soluble natural alkaloids were fabricated (evodiamine (EA) carried by fructus bruceae oil-based emulsive nanosystems, or EFEN). Fructus bruceae oil has two excipient-like properties (oil phase and stabilizer) that contribute to the formulation and one drug-like property (antitumor effects) that synergizes with the antitumor effect of EA. The properties of EFEN were compared with free EA, a blank nanoemulsion, an EA-loaded emulsive nanosystem, and a fructus bruceae oil-loaded emulsive nanosystem. For the first time, this suggests that increases in the sensitivity of lung cancer cells to poorly soluble natural alkaloids can be achieved by delivering drugs using woody oil-based emulsive nanosystems. In this study, woody oil-based emulsive nanosystems efficiently deliver poorly soluble natural alkaloids.